Relationship between self-efficacy, social support and psychological wellbeing among adolescents with physical disabilities in Lagos State, Nigeria - Jay Jay, Nwosu Eziaha James (2021)
The aim of this study was to examine the relationship between self-efficacy, social support and psychological wellbeing among adolescent with physical disability in Lagos State, Nigeria. The sample of the present study consistedof 300 adolescent students (141 males and 159 females). The age of the participants ranged between 13 to 17 years old were selected from different public secondary schools in Lagos State, Nigeria. This study applied a cross-sectional survey research design. The multistage sampling technique was used to choose the respondents. Adolescents havinga physical disability were selected as respondents. Psychological wellbeing (self-acceptance, personal growth, purpose in life, personal relationship with others and autonomy) as a dependent variable was measured using the Ryff Scales of Psychological Wellbeing (Ryff, 1989). While social support (family and friends) was measured using Multidimensional Scale of Perceived Social Support (MSPSS) (Zimet, 2010), and Self-efficacy was measured using the general Self – Efficacy scale (GSE), (Schwarzer & Jerusalem, 1995). The results of the study revealed that five dimensions of psychological wellbeing significantly correlated with social support and self-efficacy positively correlated with social support. The findings also show that, there was no significance differences in self-efficacy and psychological wellbeing for both gender except in autonomy but there was a significant difference in social support from friends between male and female. There was no mediating effect of self-efficacy on the relationship between social support and psychological wellbeing. Based on the findings of this study, it can be concluded that, social support from family and friends help to facilitate the adolescent’s advancement in manners that are healthier. The findings clearly indicate that gender does not have an impact on psychological well-being among male and female adolescents with physical disabilities in Nigeria. The findings have a range of significant consequences for parents, tutors, schools, researchers, clinicians, the Ministry of Education. Social support is needed to help develop strategies to encourage emotional intelligence and self-efficacy that address the psychological well-being of adolescents with physical disabilities